Scientific and Technological Collaboration between Defense Industries and Universities: Casual Layered Analysis Approach - Mostafa Safdari Ranjbar; Seyyed Reza Salami; Gholam Reza Tavakoli; Siamak Tahmaseby (بهبود مدیریت, 2015)
Collaboration between universities and industries has attracted policy makers and researchers for multiple decades. In our country, both in academic and practice great attempts have been done to shape a dynamic and effective collaboration between universities and industries specially defense industries. It’s obvious that the appropriate collaboration between universities and defense industries has not been formed yet. The presented solutions and designed mechanisms for transition from obstacles and challenges are insufficient and ineffective. It seems that, the lack of efficiency and effectiveness of intervention solutions for exiting from current situation is related to superficiality of solutions and this problem is rooted in superficiality of analysis, challenges and mechanisms. This research aims to by applying Casual Layered Analysis (CLA) method and exploiting the opinions of some experts from universities and defense industries, increases the depth of analysis and respectively identifies current and desired situation and prescribes mechanisms in order to transition. Findings of this research encompass current and desired situation about collaboration of universities and defense industries and mechanisms to transition in four layers: Litany, Systemic Causes, Discourse/Worldview and Myths/Metaphors.